Economic burden and health‐related quality of life associated with Prader–Willi syndrome in France. Issue 9 (13th May 2016) - Chevreul, K.; Berg Brigham, K.; Clément, M.‐C.; Poitou, C.; Tauber, M.; ,
Abstract: Background: To date, there has been no published comprehensive estimation of costs related to Prader–Willi syndrome (PWS). Our objective was therefore to provide data on the economic burden and health‐related quality of life associated with PWS in France in order to raise awareness of the repercussions on individuals suffering from this syndrome and on caregivers as well as on the health and social care systems. Method: A retrospective cross‐sectional study was carried out on 51 individuals recruited through the French PWS patient association. Data on their demographic characteristics and resource use were obtained from an online questionnaire, and costs were estimated by a bottom‐up approach. The EQ‐5D‐5L health questionnaire was used to measure the health‐related quality of life of individuals suffering from PWS and their caregivers. Results: The average annual cost of PWS was estimated at €58 890 per individual, with direct healthcare accounting for €42 299, direct non‐healthcare formal costs €13 865 and direct non‐healthcare informal costs €8459. The main contributors to PWS costs were hospitalisations and social services. Indirect costs resulting from loss of productivity in the labour market was €32 542 for adults suffering from PWS. Mean EQ‐5D utility scores were 0.4 for individuals with PWS and 0.7 for caregivers. Conclusions: Prader–Willi syndrome represents a major economic burden from a societal perspective and has a significant impact on health‐related quality of life both for individuals suffering from PWS and for their caregivers in France. These results underscore the need to develop tailored policies targeted at improving care. Likewise, a larger study collecting a broader range of medical characteristics should be undertaken to achieve more precise estimations.